Mortality in the older adults in the Federal District, 2008-2018: main causes and related factors (Research, Society and Development, 2021)
Objective: To describe the deaths of the elderly in the Federal District from 2008 to 2018 and analyze the main causes and related factors. Methodology: Time series study on older adults mortality, descriptive analysis and comparison of rates using the jonckheere-terpstra test. Results: The mean age was 76.51. Most deaths occurred between 80 years of age or older. Male sex predominated. The main causes of death were acute myocardial infarction (6.6%); pneumonia (5.2%); stroke (4.1%); malignant neoplasm of the bronchi or lungs (3%) and chronic obstructive pulmonary disease (2.6%). Higher mortality among men (p